Human Resource is being Trafficked by Luring in the World instead of Using as a Resource: An Empirical Study of Human Trafficking in Bangladesh - Rahman, Md. Motiar (Asian Business Review, 2018)
At present human resource is being trafficked by luring in the world instead of using as a resource. This heinous crime and social scar have become a global concern recently. The uneducated and innocent feeble people are illegally immigrated seeking a better future abroad but they are abused. Data have been collected from primary and secondary sources by questionnaire and interview method. The development of any country depends on the development of human resource. But today the traffickers consider human trafficking as a profitable industry. They target some illiterate workers and take them abroad by promising lucrative job as well as an attractive salary that dreams the workers standard life leading opportunity. But the workers are not given the promised job abroad. They are used as a slave, forced or bonded labor or commercial sexual exploitation. Even the workers often face isolation, sexual abuse, fear, rape that can be caused by death. But if this human resource is used properly instead of abuse, they will be a great resource for any country.